UV Astronomy 2011 2011
DOI: 10.1007/978-94-007-2573-7_34
|View full text |Cite
|
Sign up to set email alerts
|

Gravitationally lensed QSOs in the ISSIS/WSO-UV era

Abstract: Gravitationally lensed QSOs (GLQs) at 1 ≤ z ≤ 2 play a key role in understanding the cosmic evolution of the innermost parts of active galaxies (black holes, accretion disks, coronas and internal jets), as well as the structure of galaxies at intermediate redshifts. With respect to studies of normal QSOs, GLQ programmes have several advantages. For example, a monitoring of GLQs may lead to unambiguous detections of intrinsic and extrinsic variations. Both kinds of variations can be used to discuss central engi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 41 publications
(38 reference statements)
0
3
0
Order By: Relevance
“…Preliminary records of B indicated the intrinsic origin of the observed variations (see Fig. 2 of Goicoechea et al 2011), so the reverberation mapping analysis in Section 3 unveils the nature of the accretion flow and its jet connection in a distant RLAGN for the first time. In Section 4 we present our main conclusions.…”
Section: Introductionmentioning
confidence: 84%
“…Preliminary records of B indicated the intrinsic origin of the observed variations (see Fig. 2 of Goicoechea et al 2011), so the reverberation mapping analysis in Section 3 unveils the nature of the accretion flow and its jet connection in a distant RLAGN for the first time. In Section 4 we present our main conclusions.…”
Section: Introductionmentioning
confidence: 84%
“…We belong to the WSO-UV/ISSIS Science Working Group, and are involved in the preparation of a large observation program to analyse optically-bright lensed quasars in the UV (Goicoechea et al 2011) 2 . In more detail, using the CASTLES 3 and SQLS 4 databases, we selected 41 systems in the redshift interval 1 < z < 3.…”
Section: Discussionmentioning
confidence: 99%
“…First, by visual inspection of the brightness records, we found that the magnitudes of A and B strongly deviate from adjacent data. Deviations of A and B occur in the same direction 5 All pre-processed frames will be soon publicly available on the GLENDAMA archive at http://grupos.unican.es/glendama/ database/ (Goicoechea et al 2015) 6 Other PSF stars led to similar results or in opposite directions (likely due to crosstalk between both images), and exceed by more than three times the preliminary typical errors. Second, a careful data analysis indicated that either the PSF fitting of the lens system led to a large χ 2 value, the image quality was poor or both things hapenned.…”
Section: Light Curves In the R Bandmentioning
confidence: 99%